Theatre Olympics. More than Theatre. Summary reports. - Banaszak, Ewa; Pluta, Jacek; Błaszczyk, Mateusz; Kajdanek, Katarzyna (Instytut Socjologii Uniwersytet Wrocławski)
The report focuses on the cycle titled Theatre Olympics The World as a Place of Truth organized as a part of ECoC Wrocław 2016. In the research process both professional and unprofessional audience was under scrutiny. In the first part of the evaluation audiences of all sections were analysed (using a web survey). In the second part more attention was given to a case study of a cycle “More then Theatre and qualitative interviews with artists and curators were carried out.
Keywords: Theatre Olympics; ECoC Wrocław 2016